Preconception health and care policies and guidelines in the UK and Ireland: a scoping review. (November 2022) - Cassinelli, Emma H; McKinley, Michelle C; Kent, Lisa; Eastwood, Kelly-Ann; Schoenaker, Danielle; McGowan, Laura
Abstract: Background: Preconception health and care strategies can substantially improve maternal and infant outcomes, and thus optimise intergenerational health. Given the burden of high-risk preconception health and social risk factors, as well as the absence of a review of preconception health and care policies and recommendations in the UK and Ireland since 2013, an update is now warranted. We undertook a scoping review to assess the nature of and summarise preconception health and care strategies, policies, guidelines, frameworks, and recommendations available in the UK and Ireland. Methods: Searches were conducted on May 4–May 18, 2022, on Google Advanced, OpenAire, NICE, ProQuest, and relevant public health websites. The methodological process was informed by Arksey and O'Malley's work (2005) and the updated guidance for conducting Joanna Briggs Institute scoping reviews (2021). This review included grey literature resources focusing on preconception health and care in adults of reproductive age (18–44 years) as addressed in strategies, policies, guidelines, frameworks, and recommendations across the UK and Ireland. Searches on services provided in Northern Ireland, as a case study, were done and supplemented by audits with key stakeholders. Resources were included only if published, reviewed, or updated during or after 2011. Data were extracted using Microsoft Excel (MSO 365, version 2209) and NVivo (version 2020), with 10% or more of the data being double-coded, and presented using a narrative approach with thematic analysis. Findings: Relevant strategies, policies, guidelines, frameworks, and recommendations addressing preconception health and care were found (n=277). Themes included behavioural (eg, folic acid intake and smoking) and biomedical health (eg, mental and physical health conditions) and wider determinants of health (eg, ethnicity and deprivation). These themes were usually embedded within documents on other topics, rather than being the stand-alone focus. Resources also highlighted the importance of preconceptual counselling and the need for improved access to care and multidisciplinary collaborations. Interpretation: Focused efforts are needed to implement identified strategies, policies, guidelines, frameworks, and recommendations. Online platforms, schools, general practitioner consultation rooms, pharmacies, and community centres are some of the avenues suitable to promote awareness of preconception health, facilitating informed decision-making about parenthood for all individuals and encouraging risk reduction. Funding: Department for the Economy Northern Ireland, and National Institute for Health and Social Care Research Southampton Biomedical Research Centre (IS-BRC-1215-20004).